“It Could Not Be an Ordinary Labour Union”: Race, Class, Exclusion, and the Japanese Camp and Mill Workers Union, 1920–1941 - Komori, Jane (Labour / Le Travail, 2025)
This article provides a history of the Japanese Camp and Mill Workers Union (JCMWU), from its founding in 1920 until its dissolution during the World War II mass incarceration of Japanese Canadians. The JCMWU was, according to union organizer Ryuichi Yoshida, a “general union of all Japanese workers” that “could not be an ordinary labour union.” Organized along the lines of race rather than by trade or industry, the union fought struggles against bosses, business owners, state officials, and the Asian exclusion movement through a number of programs and activities. But perhaps more than anything else, the jcmwu was a political education project, centred around its newspapers, Rōdō Shūhō and Nikkan Minshū. Drawing on previously untranslated materials from these newspapers, this article takes up the extraordinary analysis and activities of the JCMWU to contribute to broader discussions about the relationship of race, labour, capitalism, and imperialism.